Analysis of the Role of Business Networks in The Development of the Kapal Coffee Café in Buah Batu Bandung - Sopiana Septiani; Septy Setiadji (Jurnal Manajemen Bisnis dan Pariwisata, 2026)
This study aimed to analyze the role of business networks in supporting the development and sustainability of Café Kapal Coffee located in Buah Batu, Bandung. The increasing competition in the culinary and café industry has encouraged business actors to strengthen networking strategies to improve operational efficiency, customer loyalty, and competitive advantage. This research employed a qualitative approach using a descriptive case study design. Data were collected through semi-structured interviews, direct observation, and documentation analysis involving café owners, employees, suppliers, and loyal customers. The data were analyzed using the qualitative analysis framework of data reduction, data display, and conclusion drawing, supported by SWOT analysis to evaluate internal and external business conditions. The findings revealed that Café Kapal Coffee relied heavily on informal business networks based on personal relationships, trust, and community involvement. These networks played a significant role in maintaining stable supplier cooperation, improving operational effectiveness, supporting promotional activities through word-of-mouth marketing, and strengthening customer loyalty. In addition, the café benefited from strategic collaborations with local communities and social networks that contributed to business sustainability and market expansion. However, several challenges were identified, including the absence of formal partnership agreements and limited utilization of digital marketing platforms. Therefore, strengthening professional networking systems and optimizing digital marketing strategies are necessary to improve long-term business competitiveness and sustainability in the increasingly competitive café industry.